Конституційний контроль як вид державного контролю: змістовно-функціональна характеристика - Буханевич Олександр Миколайович; Івановська Алла Миколаївна (Публічне право, 2019)
У статті проаналізовано сутність та функціональні особливості конституційного контролю як специфічного виду державно-правової діяльності, окреслено характерні риси конституційного контролю як виду державного контролю та визначено його основні завдання у сфері встановлення, підтримання, зміцнення і відновлення конституційного порядку. Характеризуючи конституційний контроль як вид державного контролю, автори виходили із наступних ознак державного контролю: відносини між контролюючим і підконтрольним і суб'єктом (підконтрольність), об'єкт державного контролю (законність та доцільність дій контрольованого), право органів державного контролю скасовувати рішення контрольованого. Визначено, що конституційний контроль має чітко виражений державно-правовий характер, оскільки є специфічною діяльністю державних органів, наділених спеціальною компетенцією, яка здійснюється за суворо визначеною процедурою і полягає у перевірці, виявленні, констатації та усуненні невідповідностей конституції законів, інших нормативних актів, а також дій (бездіяльності) органів публічної влади, організацій або громадських об'єднань та винесення на цій підставі рішень, що мають загальнообов'язковий і остаточний за своїм юридичними наслідками характер. The article analyzes the nature and functional features of constitutional control as a specific type of state-legal activity, outlines the characteristic features of constitutional control as a type of state control, and defines its main tasks in the area of establishing, maintaining, strengthening and restoring the constitutional order. It has been suggested that regardless of the fact that a control function is structured within a state body for which this function is not the main one, or a specialized control body is created, all control functions have common features, determined by the essence of state control. All control bodies, including bodies of constitutional control, exercise in a legal form specific functions of state power; these functions are an instrument, a means of realizing the functions of the state and are carried out on behalf of the state as a whole. Therefore, no matter what bodies exercise the functions of state control, they have a national character. Describing constitutional control as a form of state control, the authors proceeded from the following features of state control: the relationship between the controlling and the controlled and the subject (controllability), the object of state control (legality andexpediency of actions of the controlled), the right of the state control bodies to annul the decision of the controlled. It is determined that the constitutional control has a clear state-legal character, as it is a specific activity of state bodies with special competence, which is carried out by a strictly defined procedure and consists of the verification, detection, finding and elimination of inconsistencies to the constitution of laws, other normative acts, as well as actions (inactivity) of public authorities, organizations or public associations and making decisions on this basis, which have a binding and final for its legal consequences character. The analysis of the essence of constitutional control allowed the authors to conclude that constitutional control has the following features: first, this type of state control is exercised by the permanent bodies of the state for which constitutional control is the main activity, their functional purpose; secondly, it is a form of professional activity of the state; third, constitutional control, to a greater extent than other types of state control, covers the field of law-making, although it is also enforced in the field of law enforcement; fourthly, it is a specialized mechanism for the protection of the constitution of the respective state, which is carried out by means of checking, detecting, finding and eliminating inconsistencies of normative acts and actions of public authorities and their officials to the constitution, during which the bodies of constitutional control have the power to abolish uncovered inconsistencies. The key factor for characterizing the concept of constitutional control is the idea that substantiates the need for the existence of the institution of constitutional control and the specificity of its tasks, which include: ensuring the supremacy of the constitution in the internal legal system; ensuring the proximate and direct effect of the constitution; ensuring the observance of the constitution by all bodies and persons, limiting the bodies of state power in adopting unconstitutional acts; using control powers for the purpose of development of legal space within the framework of constitutional legality, creation of legal opportunities for the development of legislation within the legal field, the basis of which is enshrined in the constitution of the respective state, ensuring the stability of society through a consistent and continuous nature of its development